(untitled) (Journal of Hama University, 2026)
Water requirements for agricultural crops and irrigation scheduling using the CROPWAT program Research Summary: During the research: 1- Collecting available information from primary data on temperature, relative humidity, wind speed, sunshine hours, and basic data for calculating evapotranspiration at the Hama Agricultural Station from the beginning of 2014 to 2024. Analytical and statistical studies were then conducted. 2- Calculating the water requirements for wheat and cotton crops using the Blaney and Criddle relationship and the Thornwaite relationship, as well as calculating the water requirements and net irrigation requirements for cotton crops using the CROPWAT program. 3- As a result of using the analytical study of the results, the ratio between the calculation of the water requirement to obtain cotton by Blaney and Criddle and the Cropwat program is equal to 77%, and the ratio between the patent calculated by the Thornwaite method on the calculated requirement for cotton using the program is equal to 86%, meaning that the crop does not provide an amount of water necessary, useful and proportionate to the previous and soil, which affects the method of withdrawal on (yield) Therefore, we see the necessity of applying and using the aforementioned program to calculate the water requirements of agricultural crops and schedule irrigation.